Drying performances and milling quality of rice during industrial fluidized bed drying of paddy in Malaysia - Ibrahim, Mohd Nordin; Sarker, Md. Sazzat Hossain; Ab. Aziz, Norashikin; Punan, Mohd Salleh (Universiti Putra Malaysia Press, 2015)
Field investigation on the operation of an industrial fluidized bed paddy dryer of 25 t/h capacity available in a processing complex of Padiberas Nasional Berhad (BERNAS) of Malaysia was carried out to assess its drying characteristics, energy consumption and quality of product during two paddy harvesting seasons. A grain drying simulation model was used to predict dryer performance which can be used as a basis for improving drying operations. For the first season (August-September), average drying rate was found to be 538 kg moisture/h to reduce moisture content (mc) from 36.98± 0.89% dry basis (db) to 27.58±0.79% (db) at 100-120°C of drying air temperature with a feed rate (capacity) of 7.75 t/h. In the second season (February-March), average drying rate was found to be 435 kg moisture/h to reduce mc from 28.14 ±0.68% (db) to 22.54 ± 0.69% (db) at 78-90°C drying air temperature with a feed rate of 9.5 t/h. The thermal and electrical energy consumptions were obtained as 7.57 and 0.97 MJ/kg water removed, respectively, for the first season, while 5.92 and 1.2 MJ/kg water removed for the second season. Higher head rice yield and whiteness and lower milling recovery were achieved during the first season than the second season at acceptable milling degree and transparency. Meanwhile, simulation results indicated that the dryer performed better in terms of increased drying capacity during the second than the first season; the dryer could be operated at 150°C to achieve almost double throughput capacity up to 20 t/h for the second season, while for the first season, high mc hindered the capacity to be at or below 7.75 t/h even when using higher a temperature of 160°C to reduce moisture to the desired final moisture of 24-25% (db). proportion of slower vehicles based on users’ opinion poll.